Usuń niewymiernośc z mianownika : 2-3√2 ‾‾‾‾‾‾‾‾‾‾‾‾‾ ═ 2√2+3√3
2-3√2‾‾‾‾‾‾ ═
2-3√2 2√2 - 3√3
‾‾‾‾‾‾‾ * ‾‾‾‾‾‾‾‾‾ =2√2+3√3 2√2 - 3√3
4√2 - 6√3 - 6√2 + 18
‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾=
(2√2)^2 - (3√3)^2
-2√2 - 6√3 +18
‾‾‾‾‾‾‾‾‾‾‾‾‾=
8-18
-10
0,2√2 - 0,6√3 - 0,8
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
2-3√2
‾‾‾‾‾‾ ═
2-3√2 2√2 - 3√3
‾‾‾‾‾‾‾ * ‾‾‾‾‾‾‾‾‾ =
2√2+3√3 2√2 - 3√3
4√2 - 6√3 - 6√2 + 18
‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾=
(2√2)^2 - (3√3)^2
-2√2 - 6√3 +18
‾‾‾‾‾‾‾‾‾‾‾‾‾=
8-18
-2√2 - 6√3 +18
‾‾‾‾‾‾‾‾‾‾‾‾‾=
-10
0,2√2 - 0,6√3 - 0,8